Responses of Mytilus galloprovincialis to challenge with environmental isolates of the potential emerging pathogen Malaciobacter marinus. Issue 131 (December 2022) - Auguste, Manon; Rahman, Faiz Ur; Balbi, Teresa; Leonessi, Martina; Oliveri, Caterina; Bellese, Grazia; Vezzulli, Luigi; Furones, Dolors; Canesi, Laura
Abstract: Bacteria of the Arcobacter- like spp. represent emerging foodborne zoonotic pathogens in humans and animals. Their increasing presence in seafood, suggesting higher occurrence in seawater due to marine pollution, is raising some environmental concern. Although Arcobacter is frequently detected in diseased oysters and stressed bivalve species, no data are available so far on its potential pathogenicity or interactions with the immune system of the bivalve host. In this work, responses to challenge with two strains of Malaciobacter marinus IRTA-19-131 and IRTA-19-132, R1 and R2), isolated from adult Crassostrea gigas during a mortality event in 2019 in Spain, were investigated in the mussel Mytilus galloprovincialis . In vivo experiments were performed in larvae (48 h post-fertilization), and in adult mussels at 24 h post-injection, in order to evaluate the pathogenicity for early developmental stages, and the hemolymph immune responses, respectively. Both R1 and R2 were moderately pathogenic to early larvae, with significant decreases in the development of normal D-veligers from 10 4 and 10 3 CFU/mL, respectively. In adults, both strains decreased hemocyte lysosomal membrane stability (LMS), and stimulated extracellular defense responses (ROS production and lysozyme activity). The interactions between mussel hemocytes and M. marinus were investigated in in vitro short-term experiments (30–90 min) using the R1 strain (10 6 –10 8 CFU/mL). R1 decreased LMS and induced lysosomal enlargement, but not cell detachment or death, and stimulated extracellular ROS production and lysozyme release, confirming in vivo data. Moreover, lysosomal internalization and degradation of bacteria were observed, together with changes in levels of activated mTor and LC3, indicating phagocytic activity. Overall, the results indicate the activation of both extracellular and intracellular immune defenses against M. marinus R1. Accordingly, these responses resulted in a significant hemolymph bactericidal activity, with a large contribution of hemolymph serum. The results represent the first data on the potential pathogenicity of Arcobacter isolated from a shellfish mortality to bivalve larvae and adults, and on their interactions with the immune system of the host. Graphical abstract: Image 1 Highlights: Two Arcobacter ( M. marinus) strains were isolated from an oyster mortality event. Both strains were moderately pathogenic for early Mytilus larvae. In vivo challenge of adult mussels elicited strong immune responses in hemolymph. In vitro exposure triggered efficient intra and extracellular defenses in hemocytes.